Correlation of lateral placental location with development of preeclampsia - Gupta, Anjali; Bansal, Priyanka; Sen, Jyotsna; Singhal, Savita Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Preeclampsia is a complex clinical syndrome which involves multiple organ systems and remains the principle cause of maternal and perinatal morbidity and mortality. Preeclampsia is a disease of trophoblastic tissue. Placental abnormality is one of the initial events in patients who are destined to develop pregnancy induced hypertension subsequently. Objective of this study was to evaluate the association of laterally located placenta on ultrasound with development of preeclampsia. Methods: This prospective observational study was conducted on 200 antenatal women with singleton pregnancy at 18-24 weeks of gestation who attended antenatal clinic of obstetrics and gynaecology, PGIMS Rohtak from October 2017 to October 2018. Detailed antenatal transabdominal ultrasound along with placental location was done between 18-24 weeks of gestation in women who fitted into inclusion criteria. All the antenatal women belonged to 18-24 weeks of gestation were included in the study except those women with chronic hypertension, diabetes mellitus, renal disease, severe anaemia, thyrotoxicosis, low lying placenta, previous history of preeclampsia or eclampsia. Results: Out of 200 antenatal women, 84 had lateral placenta while 116 had central placenta. Out of these 84 women who had lateral placenta, 55 women (65.5%) developed preeclampsia and out of 116 (58%) women who had central placenta, 28 women (24.1%) developed preeclampsia. Conclusions: From the above study, we concluded that women with laterally located placenta by ultrasound at 18-24 weeks of gestation have greater risk of developing preeclampsia.